TRANSFORMING HEALTHCARE GOVERNANCE THROUGH LOCAL WISDOM: JENGAH NGAYAH-BASED TRADITIONAL HEALTH TOURISM MODEL AT TAMAN USADA BALI - Nandaka, I Ketut Tirka; Semara, I Made Trisna; Yadnya, Ida Bagus Putra; Saputra, I Putu David Adi (LPPM Universitas Jambi, 2026)
The commodification of Balinese culture in tourism and the systemic dysfunction of modern, mechanistic healthcare governance highlight a critical need for holistic healing alternatives. Although traditional health tourism (Usada) in Desa Baru, Tabanan Regency, offers significant potential as an antithesis to this issue, its management remains sub-optimal. This study aims to analyze the existing governance dynamics and design a health tourism governance model rooted in local wisdom. Employing a qualitative approach with a multi-site case study design, data were collected through participatory observation and in-depth interviews with key informants, followed by thematic analysis. The findings reveal that addressing the failure of modern medical institutions to provide equitable and empathetic care requires a fundamental paradigm shift. Consequently, this study formulates the